Genetic variations associated with the soapy flavor perception in Gorgonzola PDO cheese. (July 2022) - Concas, Maria Pina; Piochi, Maria; Cabrino, Giorgia; Colaianni, Alessia; Nardone, Giuseppe Giovanni; Gasparini, Paolo; Torri, Luisa
Highlights: Genetic analyses on soapy flavor perception in Gorgonzola cheese were performed. Subjects were grouped in soapy-tasters (66%) and non-soapy tasters (34%). Genes involved in olfactory or taste processes were found: SYT9, PDE4B, AVL9, HTR1B. A single nucleotide polymorphism near HTR1B gene affected also the liking for cheese. Soapy flavor perception was associated with rs72921001 (as found for cilantro) Abstract: Food preferences are influenced by several factors including individual differences in the physiological perception of the sensory properties and genetic factors. This study was aimed to investigate the genetic bases underlying the perception of the soapy flavor, a sensory attribute identified as a driver of disliking for blue-veined cheese. Responses on soapy flavor perception (SFP) in six Gorgonzola Protected Designation of Origin (PDO) cheese samples were collected from 219 genotyped Italians (age 18–77 y) applying a Rate-All-That-Apply (RATA) test combined with a liking test. Genome-Wide Association Studies (GWAS) were performed on three phenotypic traits: the SFP in at least one cheese (SFP_1), the number of cheese samples in which each individual perceived the soapy flavor (SFP_N) and the SFP in the cheese in which the highest number of individuals perceived the soapy flavor (SFP_P95). Results showed that 144 individuals (65.8%) perceived the soapy flavor in at least one cheese. Our analysis allowed identifying four loci that resulted shared in all the three GWAS and have been confirmed by the SFP in at least other two Gorgonzola cheese samples. Particularly, we highlighted four genes ( SYT9, PDE4B, AVL9 and HTR1B ) that are involved in olfactory or taste processes, suggesting that they could play a relevant role in determining the individual differences in the SFP. In addition, a SNP near the HTR1B gene affected also the liking for Gorgonzola PDO cheese . Overall, our work suggests possible candidate genes associated with the perception of soapy flavor, providing a starting point to better understand the individual differences in blue-veined cheese perception and expanding the current scientific knowledge in the emerging research area linking genetic individual differences to food perception and preferences.